Features of commercial litigation in the field of intellectual property - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article discusses some problems and grounds of trial in intellectual property as one of the effective ways to protect in order to recover the damage. There is an increasing number of the claims to the commercial courts of Ukraine on protection of intellectual property rights in recent years. For violation of the intellectual property rights in our state against Ukraine have been used economic sanctions by other foreign powers. Litigation of commercial courts requires further scientific studying and generalization of the issues related to the protection of intellectual property. The purpose of the article is consisted of researching of issues and grounds of disputes for the protection of intellectual property and the generalization of judicial practice of commercial courts to protect intellectual property.